PERAN KONSELING INDIVIDUAL DENGAN PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK MENGATASI SOCIAL ANXIETY SISWA KELAS X SMA NEGERI COLOMADU TAHUN PELAJARAN 2025/2026 - Damayanti, Fitri; Hera Heru Sri Suryanti; Eko Adi Putro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fitri Damayanti. THE ROLE OF INDIVIDUAL COUNSELING USING COGNITIVE BEHAVIOR THERAPY (CBT) APPROACH TO OVERCOME SOCIAL ANXIETY IN CLASS X STUDENTS OF SMA NEGERI COLOMADU ACADEMIC YEAR 2025/2026. This study aims to determine the role of individual counseling with the CBT approach in overcoming social anxiety in class X students of SMA Negeri Colomadu. This research used Guidance and Counseling Action Research (PTBK) conducted in three cycles using the Kemmis and McTaggart model. The subject was a class X-2 student (SAF) identified as having high social anxiety. CBT techniques applied were thought monitoring, cognitive restructuring, behavioral experiment, and behavioral reinforcement. Observation results showed a decrease from 80% (pre-cycle) to 45% (cycle III), a total reduction of 35%. The social anxiety scale decreased by 31%, from 81% (high) to 50% (low). Individual counseling with CBT effectively helps students identify and change negative thought patterns that trigger social anxiety and improves adaptive social behavior.